Effect of sheet pile wall on the load-settlement behaviour of square footing nearby excavation. Issue 2 (4th March 2023) - Ahmad, Hussein; Hoseini, Mohammad Hosein; Mahboubi, Ahmad; Noorzad, Ali; Zamanian, Mostafa
ABSTRACT: Due to the shortage of urban land, new buildings are constructed adjacent to old buildings. In this regard, there is limited information about the behaviour of the shallow foundations adjacent to the excavation. In this research, a series of experimental and numerical studies are conducted on reinforced and unreinforced granular soils adjacent to excavation loaded with square footings. The experimental results are in good agreement with the numerical study. Numerical investigations were carried out on sandy excavation by varying the footing distance from the edge of the different granular excavations. It was found that by using three reinforcing layers, the ultimate bearing capacity would increase. Additionally, excavation has no significant effect in the vicinity of 4B, in which B is the footing width. Furthermore, the need to build new large buildings in the vicinity of each other has reduced the distances between square footings and, as a result, has created the phenomenon of interference in the footings and excavation. This occurs through the interference of wedges and rupture surfaces. Since this phenomenon bears a substantial result on the bearing capacity of shallow footings, this work investigates the effect of interference of ruptured wedges on the carriage capacity, settlement, and deformation of square footings. The optimum interference factor is defined at spacings of 2B and 3B for dense and loose reinforced sands, respectively. Furthermore, by including three continuous geogrid layers underneath two square footing interferences, their behaviour will be improved.